2017
DOI: 10.1042/bcj20170436
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between σ region 3.2 and secondary channel factors during promoter escape by bacterial RNA polymerase

Abstract: In bacterial RNA polymerase (RNAP), conserved region 3.2 of the σ subunit was proposed to contribute to promoter escape by interacting with the 5'-end of nascent RNA, thus facilitating σ dissociation. RNAP activity during transcription initiation can also be modulated by protein factors that bind within the secondary channel and reach the enzyme active site. To monitor the kinetics of promoter escape in real time, we used a molecular beacon assay with fluorescently labeled σ subunit of RNAP. We show that subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…The data in Figure 3B and D show that fraction of open complexes that were unable to escape was ∼15–30% and no clear pattern of dependence on ITS could be detected. In the presence of GreB a modest reduction of the fraction of complexes that did not escape could be observed ( Figure S2C, Supplementary Information ), in agreement with previously proposed role of backtracking in the formation of non-productive initiation complexes ( 31 ) and recent kinetic investigation ( 46 ). Decrease of open complex stability ( 47 ) could also contribute to the observed effect of GreB on fraction of complexes that did not escape.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The data in Figure 3B and D show that fraction of open complexes that were unable to escape was ∼15–30% and no clear pattern of dependence on ITS could be detected. In the presence of GreB a modest reduction of the fraction of complexes that did not escape could be observed ( Figure S2C, Supplementary Information ), in agreement with previously proposed role of backtracking in the formation of non-productive initiation complexes ( 31 ) and recent kinetic investigation ( 46 ). Decrease of open complex stability ( 47 ) could also contribute to the observed effect of GreB on fraction of complexes that did not escape.…”
Section: Resultssupporting
confidence: 90%
“…The fact that slow kinetic component was not completely eliminated by GreB ( Figure S2A and B, Supplementary Information ) may indicate presence of additional mechanisms for delaying escape that do not respond to GreB. Recent report on promoter escape kinetics ( 46 ) that used real-time escape assay utilizing fluorescence signal of a probe incorporated into σ subunit also found that generally GreA and GreB increased the rate of escape but on some templates GreB could also inhibit escape. While the observed effects of GreB on escape rates are consistent with the presence of significant amounts backtracking complexes during escape under our experimental conditions, a detailed study of GreA/GreB effects on escape (and template-sequence dependence of these effects) will be needed to fully understand these effects.…”
Section: Resultsmentioning
confidence: 95%
“…The structure predicts that the σ A 3.2 finger has to be displaced by an RNA molecule of > 4nt length and that the σ A 3.2 loop in the RNA exit channel has to be cleared during the promoter escape process. The interactions observed in the σ A -RPo structure underscore the key role of the σ A 3.2 on abortive production, pausing, and promoter escape in transcription initiation 28,29,49,50 . In our crystal structures of σ H -RPo, we show that σ H 3.2 guides the template ssDNA into the active site cleft and forms interactions with template ssDNA ( Figure 3D and 5E).…”
Section: Discussionmentioning
confidence: 81%
“…Domain σ3.2 reaches into the RNAP active site cleft and "pre-organizes" template ssDNA 24 . Domain σ3.2 also blocks the path of the extending RNA chain (> 5nt) 26,27 thereby contributing to both initial transcription pausing 28 and promoter escape 29,30 .Each category of known ECF σ factors recognizes promoters bearing a unique sequence signature at the -35 and the -10 elements 10,31 . In contrast to the high tolerance to sequence variation at the -35 and the -10 promoter elements exhibited by the primary σ factor, the ECF σ factors have stringent requirements for sequence identity in the -35 and the -10 elements and for spacer length between these two elements through an unknown mechanism 8, 32 .Although both the primary and ECF σ factors recognize the -35 element via σ4 and recognize the -10 element via σ2, the protein sequences of these two domains are not well conserved, and the consensus sequences of the two corresponding DNA elements vary.…”
mentioning
confidence: 99%
See 1 more Smart Citation